Plasmonic Nanotweezers and Nanosensors for Point‐of‐Care Applications (Advanced Optical Materials 13/2021). Issue 13 (5th July 2021) - Peng, Xiaolei; Kotnala, Abhay; Rajeeva, Bharath Bangalore; Wang, Mingsong; Yao, Kan; Bhatt, Neel; Penley, Daniel; Zheng, Yuebing
Abstract : In article number 2100050, Yuebing Zheng and co‐workers review the progress in developments and applications of plasmonic nanotweezers and nanosensors where the plasmon‐enhanced light–matter interactions at the nanoscale improve the optical manipulation and analysis of biological objects. In the context of plasmofluidics, which merges plasmonics and fluidics, the authors discuss the integration of plasmonic nanotweezers and nanosensors with microfluidic systems for point‐of‐care (POC) applications and provide perspectives on the challenges and opportunities in further developing and applying the plasmofluidic POC devices.